1972
DOI: 10.1111/j.1445-5994.1972.tb03071.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Autoimmune Diseases

Abstract: Summary: Disease associations provide useful aetiological clues in relation to diseases of unknown causation; this holds particularly for auto‐immune disorders which tend to occur together in individuals and in related family members. Nine patients suffering from both multiple sclerosis and presumed auto‐immune disorder were found from a survey of case records of 326 patients with multiple sclerosis admitted to a large city hospital between 1955 and 1970. There was autoimmune disease affecting the thyroid gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

1974
1974
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 24 publications
2
26
0
1
Order By: Relevance
“…Considering MS, in 1972 an initial uncontrolled retrospective study of 326 Australian patients revealed coexistence in nine with some other autoimmune disease, including thyroiditis in four [45]. A later case-controlled study of 117 patients and their relatives with a questionnaire design revealed moderate increases in prevalence of other autoimmune diseases including thyroiditis and RA in patients and/or relatives [46].…”
Section: Autoimmune Diseases For Which Coexistence Is Debatable: Ms Amentioning
confidence: 95%
“…Considering MS, in 1972 an initial uncontrolled retrospective study of 326 Australian patients revealed coexistence in nine with some other autoimmune disease, including thyroiditis in four [45]. A later case-controlled study of 117 patients and their relatives with a questionnaire design revealed moderate increases in prevalence of other autoimmune diseases including thyroiditis and RA in patients and/or relatives [46].…”
Section: Autoimmune Diseases For Which Coexistence Is Debatable: Ms Amentioning
confidence: 95%
“…Several studies have evaluated the occurrence of autoimmune thyroid disease (AIT) in the multiple sclerosis (MS) population, reporting prevalences ranging from 0.92 to 13.9% [1,2]. Some of these studies suggested that AIT is more common in individuals with MS as compared to the findings expected for the general population [3,4,5]; however, most of these studies did not use contemporaneous control groups.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, four of the nine patients were women and ATAbs seropositive. To our knowledge, two cases of classic MS associated with asymptomatic chronic autoimmune thyroiditis have been reported from Spain [17] and New Zealand [1]. Thus serum ATAbs are commonly detected, but not exclusively in OSMS.…”
Section: Discussionmentioning
confidence: 92%